The mathematical sentence can be written as:
5/(a + b).
Here we have a mathematical sentence and we want to write as an expression.
"5 divided by the sum of a and b".
The sum of a and b is just written as:
a + b
And we must have 5 divided by that, so we just write this like a quotient:
5/(a + b).
This is the expression that is equivalent to the mathematical sentence.
If you want to learn more about quotients, you can read:
5/a+b
sum means addition which divided obviously means division so....
B- (-24) divided by 6 + 2
C- 36 divided by(-4) + 7
D- (-32) divided by 8 - 4
B) 8
C) 20
D) 1806
2. Given the sequence is defined by the explicit definition tn=2^n-n, find the 5th term of the sequence. (ie t5)
A) 5
B) 10
C) 27
D) 32
Answer:
1 C) 20,
2 C) 27,
The sequence is 3,5,9,17,33
Answer:
20,
27,
3,5,9,17,33
Step-by-step explanation:
Answer:
q=35
Step-by-step explanation:
x2 - 12x + q = 0
Let the two roots be r and r+2.
Factor the quadratic expression:
(x - r)[x - (r + 2)] = 0
Expand, simplify, group like terms, and get
x2 - 2(r + 1)x + r(r + 2) = 0
Compare to
x2 - 12x + q = 0
and set equal the coefficients of like terms:
Coefficient of x:
-2(r + 1) = -12 ⇒ r + 1 = 6 ⇒ r = 5
(Then the other root is r + 2 = 5 + 2 = 7)
Constant term:
r(r + 2) = q ⇒ 5(5 + 2) = q
q = 35
Test the solution:
(x - 5)(x - 7) = x2 - 12x + 35
With two roots differing by 2, you get an equation of the form
x2 - 12x + q = 0
with q = 35.
Answer:
13
Step-by-step explanation: